Criteria for Locating Temporary Shelters for Refugees of Conflicts: A Systematic Review - Reza Ramazani; Abbaas Ostadtaghizadeh; Arezoo Yari; Ahmad Ali Hanafi-Bojd; Ahmad Soltani; Shah Bakhti Rostami; Ahad Heydari (Tehran University of Medical Sciences, 2022)
Background: We aimed to identify the indicators and criteria to locate temporary shelters for conflict refugees. Methods: This systematic review evaluated the full-text of the related articles in international electronic databases, such as Web of Science, Scopus, PubMed, Cochran, and Google Scholar from the beginning and without time limit to 1 June 2019. In addition, this search was based on a strategy developed by the researchers. The studies were selected regardless of their methods and two data extraction forms were used to extract the most relevant and important information. Results: Among 10124 cases of primary documents, 38 articles were selected, and 25 articles were analyzed in full-text. Totally, 45 indicators were identified and classified into two main categories of physical and non-physical indicators with six subcategories of land ownership, host government, access to infrastructures, site safety, land characteristics, and economic, social, and cultural considerations. Conclusion: The selection of temporary shelters for the conflict refugees requires the identification of all the specific influential factors not properly addressed. The final indicators obtained in our review could be incorporated into the development of the models required in this regard.